Nothing but NET: A review of norepinephrine transporter expression and efficacy of (131)I-mIBG therapy - Streby, Keri A (Pediatr Blood Cancer, 2015)
Neuroblastoma is unique amongst common pediatric cancers for its expression of the norepinephrine transporter (NET), enabling tumor-selective imaging and therapy with radioactive analogues of norepinephrine. The majority of neuroblastoma tumors are avid for (123)I-metaiodobenzaguanidine (mIBG) on imaging, yet the therapeutic response to (131)I-mIBG is only 30% in clinical trials, and off-target effects cause short- and long-term morbidity. We review the contemporary understanding of the tumor-selective uptake, retention, and efflux of meta-iodobenzylguanidine (mIBG) and strategies currently in development for improving its efficacy. Combination treatment strategies aimed at enhancing NET are likely necessary to reach the full potential of (131)I-mIBG therapy.